Self-awareness and transcendence in the management of human talent in educational institutions in post-pandemic scenarios - Cabrales Salazar, Omar; Bermúdez, Jorge Antonio (Revista Brasileira de Política e Administração da Educação - Periódico científico editado pela ANPAE, 2022)
The article emphasizes the importance of three human dimensions in optimizing management skills to guide teachers and students toward better states of well-being at work and overcoming the educational crisis left by the 2020/21 pandemic. It’s based on the human potential strengths (Aspinwall & Staudinger, 2003) like an essential attribute and role to an organization’s intangible assets (Pike et al, 2005) and the model of happiness or meaningful life (Frankl, 1985; Seligman, 2003). To improve human educational talent administration, a principal must know what the dimensions of the human condition are, and how to develop capacities to manage them to implement strategies resulting in the institution’s well-being. We conclude by inducing the implementation of optimism, as it is a strategy needed to face the crisis left by the lockdown, the desertion of thousands of students, and technology increasingly replacing teachers.